STUDY AND MODELING OF THE DISINTEGRATION KINETICS OF COATED PAPER - Josep Puig; M. Àngels Pèlach; Nour-Eddine El Mansouri; Manuel Alcalà; Jean-Claude Roux; Pere Mutjé (BioResources, 2011)
The disintegration of recovered paper is the first operation in the preparation of recycled pulp. It is known that the defibering process follows a first order kinetics from which it is possible to obtain the disintegration kinetic constant (KD) by means of different ways. The disintegration constant can be obtained from the Somerville index results (%ISV) and from the dissipated energy per volume unit (SS). The %ISV is related to the quantity of non-defibrated paper, as a measure of the non-disintegrated fiber residual (percentage of flakes), which is expressed in disintegration time units. In this work, disintegration kinetics from recycled coated paper has been evaluated, working at 20 rev/s rotor speed and for different fiber consistency (6, 8, 10, 12, and 14%). The results showed that the values of experimental disintegration kinetic constant, KD, through the analysis of Somerville index, as function of time, increased with the disintegration consistency. Therefore, as consistency increased, the disintegration time was drastically reduced. The calculation of the disintegration kinetic constant (modeled KD), extracted from the Rayleigh’s dissipation function, showed a good correlation with the experimental values using the evolution of the Somerville index or with the dissipated energy.